2012
DOI: 10.1111/ipd.12010
|View full text |Cite
|
Sign up to set email alerts
|

Oral health condition and treatment needs among young athletes with intellectual disabilities in Indonesia

Abstract: The results suggest that there is an elevated oral treatment need in Indonesian Special Smiles population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 15 publications
1
37
0
2
Order By: Relevance
“…Through the quality assessment (Table ), the score ranged from 4 to 7 out of 10 possible points. Of the 16 studies that underwent a risk of bias assessment, eight (50%) were considered to have a moderate risk of bias and eight (50%) were considered to have a high risk of bias …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Through the quality assessment (Table ), the score ranged from 4 to 7 out of 10 possible points. Of the 16 studies that underwent a risk of bias assessment, eight (50%) were considered to have a moderate risk of bias and eight (50%) were considered to have a high risk of bias …”
Section: Resultsmentioning
confidence: 99%
“…A population sample of 35,732 individuals was enrolled in this review, ranging from 160 to 14,319 athletes. Thirteen articles were cross‐sectional studies, another study was a retrospective, one study did not report the design, and Feldman et al . was a pilot study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies regarding oral health status of child athletes mainly focus on children with intellectual disabilities [29][30][31][32]. Thriandini et al [29] screened child athletes with a mean age of 13.4 and observed that almost 70% of the athletes had visible untreated caries. Oredugba et al [30) conducted a similar study in Nigeria and reported that 22.4% of the child athletes had untreated caries lesions.…”
Section: Discussionmentioning
confidence: 99%